George's marvelous medicine - Dahl, Roald (New York : Penguin Group, 1981)
George decides that his grumpy, selfish old grandmother must be a witch and concocts some marvelous medicine to take care of her.
Keywords: Grandmothers -- Fiction; Magic -- Fiction